Inovasi Pembelajaran Pendidikan Agama Islam Menghadapi Tantangan Globalisasi - Ismail Mulias; Amaluddin Amaluddin (Journal of Humanities, Social Sciences, and Education, 2025)
Globalization brings very rapid changes in various aspects of life, including in the world of education. Islamic Religious Education (PAI) as an integral part in the formation of character and morals of the younger generation faces major challenges to adapt to the dynamic developments of the times. Learning innovation is an important solution so that PAI remains relevant and able to answer the needs of students in a global context. This literature study aims to identify various PAI learning innovations that are effective in facing the challenges of globalization based on studies of various current research and scientific articles. The method used is a literature study with data search techniques through relevant journals, books, and online sources. The results of the study show that there are five important points of learning innovation, namely: the use of digital technology as a learning medium, the development of contextual and thematic curriculum, the application of interactive learning methods, strengthening moral values ​​and character through a multidisciplinary approach, and increasing the competence of PAI teachers in mastering modern technology and pedagogy. In conclusion, adaptive and integrative PAI learning innovations are needed to equip students to face the challenges of globalization while maintaining religious and cultural values.